Molecular Cytogenetic Investigations in a Novel Chromosomal Abnormality of t(10;15)(q22;q22) in a Pediatric Precursor-B-Acute Lymphoblastic Leukemia Patient - Prerana Bhandari; Firoz Ahmad; Rupa Dalvi; Prajakta Kokate; Bibhu Ranjan Das; Swarna Mandava (Journal of Hematology and Oncology Research, 2014)
Acute lymphoblastic leukemia (ALL) is a rapid form of leukemia characterized by clonal proliferation and accumulation of immature hematopoietic stem cells of the lymphoid lineage in the bone marrow as well as peripheral blood. Chromosomal aberrations identified in childhood ALL have an important role in disease diagnosis, prognosis and management. We present the results of hematologic, immunophenotypic, cytogenetic, FISH and Multiplex RT-PCR analysis of a 6-year-old boy diagnosed with B-cell precursor Acute Lymphoblastic Leukemia (BCP- ALL). In this study, we identified a novel chromosomal translocation t(10;15)(q22;q22) by cytogenetic and FISH analysis. To the best of our knowledge, this is the first report of this novel chromosomal translocation in this subset of ALL and has not yet been reported elsewhere. This rearrangement may include certain cancer associated tumor suppressor gene(s) or genes involved in apoptosis and transcription regulation, which on loss of normal function may lead to leukaemogenesis.
Keywords: B-cell precursor Acute Lymphoblastic Leukemia